VARIASI BAHASA DAYAK AHE DALAM KOMUNIKASI MAHASISWA GENERASI Z UNIVERSITAS PGRI PONTIANAK - Fitri Wulansari; Mellany Rahmawatyi; Rajwa Ain Sahahada; Riska Febriani; Yulita Ningsih; Dini Hajjafiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the variation in the use of the Dayak Ahe language among Generation Z students at PGRI University of Pontianak, particularly in the casual and intimate styles. The research question is how these two styles are used in students’ daily interactions. This study aims to describe the forms of the casual and intimate styles in the use of the Dayak Ahe language in the communication of Generation Z students. The method used is qualitative descriptive. The research data consists of spoken utterances obtained from informants who are active speakers of the Dayak Ahe language through focused observation, interviews, and note-taking. Informants were selected based on specific criteria relevant to the research objectives. Data analysis drew upon Martin Joos’s theory of language variation, focusing on the casual and familiar varieties, through systematic stages of grouping, classification, and interpretation of the data. The results indicate that the casual variety is characterized by the use of simple language, a departure from standard forms, and the use of general greetings in informal situations. Meanwhile, the familiar variety is characterized by more personal language, shorter speech forms, and the use of specific forms of address that reflect the closeness of the relationship between speakers. Thus, the linguistic variation of Dayak Ahe in Generation Z students’ communication reflects an adaptation of language use based on.